Macedonia and Identity Politics After the Prespa Agreement - Neofotistos, Vasiliki P. (Taylor & Francis, 2021)
This book explores issues of national identity, history, and language in light of the 2018 Prespa Agreement. Designed to resolve a protracted and bitter dispute, the agreement signed by the Macedonian and Greek foreign ministers on the banks of the Prespa lake stipulated that the Republic of Macedonia change its name to the Republic of North Macedonia.The chapters examine the social, political, and economic conditions and events that led to the agreement and the implications and consequences for identity politics in the region. Consideration is given to the ways in which, and the reasons why, identity/identities, difference/differences, modes of belonging, and experiences of injustice and discrimination have been mobilized. By focusing on the Prespa Agreement, the collection also offers valuable insight into the processes involved in (re)making boundaries, (re)defining ethnic and national identities, (re)inventing citizenship, and (re)writing national histories. Bringing together expert contributors with intimate knowledge of, and long-term engagement with, the region, this volume will be of interest to scholars and students of anthropology, Slavic and East European studies, history, and international relations.